1995
DOI: 10.1152/ajpgi.1995.269.1.g167
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ waves are organized among hepatocytes in the intact organ

Abstract: Hormone-induced increases in cytosolic Ca2+ (Cai2+) begin as Cai2+ waves in cells isolated from most types of tissue (1, 11), but whether such waves actually occur in vivo is unknown. To investigate this, we examined vasopressin-induced Cai2+ signals in hepatocytes within the perfused rat liver. Using confocal fluorescence video microscopy, we found that increases in Cai2+ began as waves that usually originated in hepatocytes near central venules, then spread opposite to the direction of blood flow, to hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
86
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 0 publications
7
86
0
Order By: Relevance
“…A large literature supports the idea that oscillatory changes in signaling molecules (e.g., Ca, cAMP) convey information distinct from changes in steady-state levels (Hajnóczky et al, 1995;Jafri and Keizer, 1995;Dupont et al, 2000a;Breitwieser, 2006), and that such oscillations occur across systems of coupled cells (cf., Nathanson et al, 1995;Robb-Gaspers and Thomas, 1995;D'Andrea and Vittur, 1996;Rottingen et al, 1997;Tordjmann et al, 1997;Dupont et al, 2000b,Ravier et al, 2005Haddock et al, 2006). In many cases, intercellular spread of the oscillatory signal has been shown to be dependent on junctional, as opposed to paracrine, communication.…”
Section: Signaling Consequences Of Different Molecular Permeabilitiesmentioning
confidence: 99%
“…A large literature supports the idea that oscillatory changes in signaling molecules (e.g., Ca, cAMP) convey information distinct from changes in steady-state levels (Hajnóczky et al, 1995;Jafri and Keizer, 1995;Dupont et al, 2000a;Breitwieser, 2006), and that such oscillations occur across systems of coupled cells (cf., Nathanson et al, 1995;Robb-Gaspers and Thomas, 1995;D'Andrea and Vittur, 1996;Rottingen et al, 1997;Tordjmann et al, 1997;Dupont et al, 2000b,Ravier et al, 2005Haddock et al, 2006). In many cases, intercellular spread of the oscillatory signal has been shown to be dependent on junctional, as opposed to paracrine, communication.…”
Section: Signaling Consequences Of Different Molecular Permeabilitiesmentioning
confidence: 99%
“…In some of these cell systems, the source and potential physiologic role of extracellular ATP are unclear. ATP can be released from mouse fibroblasts (2) or rat basophilic leukemia cells (3) (6,7), and this also is thought to be due in part [Arg8]vasopressin, phenylephrine, and propidium iodide were from Sigma; fluo-3/AM was from Molecular Probes; suramin was from Biomol (Plymouth Meeting, PA); and indodicarbocyanine (Cy5) was from Biological Detection Systems (Pittsburgh). All other chemicals were of the highest quality commercially available.…”
mentioning
confidence: 99%
“…Furthermore, hepatocyte ATP receptors are sensitive to both ADP (20) and UTP (15), and bile duct cell ATP receptors are sensitive to UTP (10,11). Therefore, an alternative possibility is that ADP or UTP is the intercellular mediator of the mechanically induced (6,21), but considerably slower than the wave speed of greater than 100 ,um/sec that can be seen in isolated hepatocyte couplets (5) and intact liver (6) ATP release from cells are controversial. Hypoxia induces ATP release from intact perfused hearts (26), isolated cardiac myocytes (27), and erythrocytes (27) …”
mentioning
confidence: 99%
“…This cellular model was used because the morphological and functional properties typical of liver tissues are preserved. Thus, vasopressin-induced calcium oscillation had been observed both on intact perfused liver (Nathanson et al 1995;Robb-Gaspers and Thomas 1995) and on hepatocyte multiplets reported by our laboratory (Combettes et al 1994;Tordjmann et al 1997Tordjmann et al ,1998. Such studies have been performed to improve our understanding of the spatiotemporal organization of the vasopressin-stimulated calcium wave.…”
mentioning
confidence: 85%